Synthesis and Characterization of Antimony Oxide Doped Cobalt Oxide by Rheological Phase Method - ALEMI, ABDOLALI; KHANDAR, ALIAKBAR; EKHTIARY KOSHKY, FATEMEH (Asian Journal of Chemistry, 2010)
Antimony doped cobalt oxid nanoparticles with composition SbxCo3-xO4 (0 ≤ x ≤ 0.024) were synthesized by rheological phase reaction and pyrolysis method. The products were characterized by X-ray powder diffraction, fourier transform infrared spectrum, scanning electron microscope, thermogravimetric analysis and simultaneous differential thermal analysis. Calcination of the precursor at 500ºC resulted in the formation of antimony doped cobalt oxide nanoparticles of 45 nm in crystal size. Effect of calcination temperature on antimony doped Co3O4 crystal size was discussed.